Strong relationships between inflammation, atherosclerosis and end stage renal disease - Tripathi, Gaurav; Borkar, Minal; Ahmad, Fahim; Swaroop, Sachit; Singh, Janmejay; Sankhwar, SN (Asian Journal of Medical Sciences, 2011)
End-stage renal disease (ESRD) is characterized by an exceptional mortality rate, much of which is the result of cardiovascular disease (CVD). Although traditional risk factors are common in ESRD patients, they may not be sufficient alone to account for the high prevalence of CVD in this condition. Recent evidence demonstrates that chronic inflammation is a common feature in ESRD patients and it may cause malnutrition and progressive atherosclerotic CVD by several pathogenetic mechanisms. The causes of inflammation in ESRD are multifactorial and, while it may reflect underlying CVD, an acute-phase reaction may also be a direct cause of vascular injury by several pathogenetic mechanisms. There is strong evidence that inflammatory markers are closely linked to ESRD. There seems to be a strong evidence of inflammatory markers, inflammation and atherosclerosis in ESRD patients and it is likely that proinflammatory cytokines and the genetic polymorphism in these cytokines may be important players in this scenario. Key Words: Cytokines; ESRD; Inflammation; Polymorphisms; CVD DOI: 10.3126/ajms.v2i1.3731 Asian Journal of Medical Sciences 2 (2011) 46-48